Forward looking needs systematised megatrends in suitable granularity. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to inquire about the applicability of the concept of granularity to the necessity of future research or – as often called in the European Union – forward looking (FL). After theoretical deliberation, it uses a planned world‐wide information system as a case study for applying the notion of granularity regarding economic sectors, time steps, geographic regions and correlations for energy, water, land use and several other drivers of global change.Design/methodology/approach – A planet‐wide information system might optimally include areas such as human development indicators, water demand and supply and deforestation issues. A short literature analysis on "granularity" shows this concept to have a highly culturally determined and constructivist nature.Findings – The spatial, temporal and sectoral granularity of data presentation strongly impacts conclusions and considerations while looking forward. Hence, granularity issues are of key importance for the question of which megatrends are ultimately discerned as most relevant.Practical implications – These findings may impact the regular report on global megatrends authored by the European Environment Agency, as well as world‐wide energy and emission scenarios and technological foresight, such as the "Global Change Data Base" as a next step of research.Social implications – In future research, the step from purely quantitative perceptions towards structural perceptions, pattern recognition and understanding of system transitions might be facilitated. The FL statements of larger companies might be diversified, enlarged in scope and use deeper structural understanding.Originality/value – Earlier databases tend to have been focused on one or several single disciplines; the present approach, however, attempts transdisciplinarity and a multiparadigmatic approach. Acknowledgements : The author wishes to express his gratitude to two professional language reviewers, Mrs Andrea Lyman and Mr Alun Brown (internationally based, www.andrea‐lyman.com) for highly successful decade‐long cooperation.